2013
DOI: 10.1016/j.sjopt.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating ability of spectral domain optical coherence tomography in different stages of glaucoma

Abstract: RNFL thickness measured with SD-OCT could discriminate the three stages of glaucoma. RNFL loss can be correlated to visual field loss. Future OCT-based staging of glaucoma, adjunctive to perimetry is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Moreover, this present study data are in accordance with another study in which they noted that normal controls had significantly higher RNFL thickness when compared with glaucoma patients and those with more severe disease had significantly thinner RNFL (6) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, this present study data are in accordance with another study in which they noted that normal controls had significantly higher RNFL thickness when compared with glaucoma patients and those with more severe disease had significantly thinner RNFL (6) .…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the present study found that RNFL thickness has a good diagnostic value for diagnosis of glaucoma and for differentiating moderate from mild glaucoma and severe from moderate glaucoma. This is in agreement with the study of Elbendary and Helal (6) and with a recent metaanalysis performed by Michelessi et al (12) . The authors included prospective and retrospective cohort studies and case-control studies that evaluated the accuracy of OCT for diagnosing glaucoma.…”
supporting
confidence: 93%
“…The diagnostic power of the each Scheimpflug parameter was graded according to the AUC value as follows; excellent (0.90-1.00), good (0.80-0.89), fair (0.70-0.79), poor (0.60-0.69) and worthless (0.50-0.59). The ROC curve plots the true positives (sensitivity) against the false positives (100-specificity) for different threshold values [14]. Values on the ROC curve, which indicated best sensitivity-specificity pair, were accepted as the cut points [14].…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve plots the true positives (sensitivity) against the false positives (100-specificity) for different threshold values [14]. Values on the ROC curve, which indicated best sensitivity-specificity pair, were accepted as the cut points [14]. At 95% confidence interval, a P value less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In 30 normal Egyptian eyes, the RNFL thickness was 110 μm, and in 150 glaucomatous eyes, it was 80 μm. 21 Thus, even among Arabs, RNFL thickness varied between the Saudi and Egyptian communities. In normal and glaucomatous eyes of the Arab population, macular thickness parameters measured by OCT are presented perhaps for the first time in our study.…”
Section: Discussionmentioning
confidence: 99%